Determination of the In Vitro Cytotoxic Activities of Several Coumarin Derivatives on Neuroblastoma Cell Lines With In Silico Inhibitory Effects on CDK9, VEGFR2 and EGFR Proteins and ADME Studies - Seyhan, E; Celikezen, FC; Sarac, K; Aslan, ME; Oner, S; Turkez, H (Cell Biochemistry And Function)
Due to their stable nature and medical applicability properties, coumarin derivatives have fascinated medicinal chemists in the discovery of novel therapeutics. In this study, the cytotoxic/anticancer properties of some newly synthesized coumarin derivatives were aimed at designing, synthesizing, and examining cultured human neuroblastoma cells. Moreover, molecular docking studies were carried out to determine the potential mechanism. In addition, ADMET properties were evaluated to examine the drug-likeness of newly designed coumarin derivatives. To detect the cytotoxic action of compounds, 3-(4,5-dimethylthiazol-2-yl)-2,5 2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) release assays were carried out. In addition, Hoechst 33258 staining was used to detect abnormal nuclear structures. In silico, the estimates for all compounds (3a-3c) used in the study revealed that they possessed desirable physicochemical properties for bioavailability. The results of our study showed that all tested compounds exhibited remarkable cytotoxic effects on human neuroblastoma cell lines (p < 0.05). Additionally, among the compounds tested, 3a and 3c showed selective effects on neuroblastoma cells effectively at all tested concentrations. However, it was found that the selective feature of 3b, unlike the others, was concentration-dependent. Our findings clearly showed that novel coumarin derivatives exerted potent and selective anticancer effects. Results of molecular docking studies were in parallel with in vitro studies. Unlike the majority of hybrid coumarin derivatives reported in anticancer research, the present study introduces minimalist, heteroatom-free coumarins bearing bulky aliphatic substituents. These compounds demonstrated selective cytotoxicity against SH-SY5Y neuroblastoma cells and a favorable multi-target binding profile, highlighting a distinct hydrophobic volume-based SAR. As a result, the obtained data exhibited that all used molecules may be good multitarget drug alternatives for the treatment of neuroblastoma.
Keywords: ADME; antican; cercoumarin; cytotoxicity